A distinguished scientific field? Pursuing resources and building institutions for engineering research in Sweden, 1890–1945. (1st October 2016) - Björck, Henrik
Abstract: The perennial issue of the relations between science and technology and society is a backdrop to this study of material, symbolic and economic foundations of engineering science in Sweden. It analyzes three cases of institutional reform from the first half of the twentieth century that were essential to the formation of engineering research as a distinct and respected scientific field. Taking the intersection of institutional and linguistic analysis as a starting point, two intertwined processes are followed: the drawing of boundaries by different actors that delineated the new kind of research, and the struggle over resources for the institutions that could enable this research. The institutional reforms are placed in context, relating arguments by the proponents of engineering research to the politicians and university academics who were in control of various resources. It is suggested that an institutionalist perspective enunciated in terms of form and content is a productive interpretive possibility.